Theological Construction of the Muslim Community in Deli Serdang - Fatimah Syari Lubis (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2019)
The problem that emerged from this research is how to understand the theological style and theological relations with the work ethic of the Muslim community in the Sei Rotan Village of Deli Serdang District. Finding in this research explains that (1) the understanding of the theology of Muslim society covering the Muslim community in the Sei Rotan Village has a different theological style of theological pattern. Such as Mujri’ah, Mu‘tazilah, and Ash‘ariyah theological style. This is because the level of their knowledge about theology in Islam is very limited. The factor of education and most of the people are graduated from junior and senior high school, and there are also graduates from S1 and S2. Moreover, when dealing with religious issues, most people only examine the general discussion, such as the discussion of the properties of god, morals, prayers, fasting, dhikr, patience, and study related to fiqh themes. (2) the relation of theology and work ethic of the Muslim community, which will be discussed in this matter, among others: the teachings of religion (theology) has influenced the work ethic of society. According to some Muslims, the work is merely an economic activity. (3). The impact of theology on the Muslim community's personality, among others, religion has a positive impact, such as the more spirit in worship. So, the more patient, sincere, the calmer the soul of his faith, and religion invite his followers to live more discipline in all things. The negative impact of theology does not exist because the theological teachings, according to the Muslim community in the Sei Rotan Village, always invite the teachings of kindness.